2006
DOI: 10.1002/hyp.5895
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of soil moisture patterns in forested and suburban catchments in Baltimore, Maryland, using high‐resolution photogrammetric and LIDAR digital elevation datasets

Abstract: Abstract:Field observations of near-surface soil moisture, collected over several seasons in a watershed in suburban Maryland, are compared with values of the topographic soil moisture index generated using digital elevation models (DEMs) at a range of grid cell sizes from photogrammetric and light detection and ranging (LIDAR) data sources. A companion set of near-surface soil moisture observations, DEMs and topographic index values are also presented for a nearby forested catchment. The degree to which topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 25 publications
4
55
2
Order By: Relevance
“…In general, these studies found that higher-quality vertical information results in appreciable improvements in the representation of topographic surfaces, more accurate delineations of hydrologically relevant parameters and more appropriate model outputs, especially regarding spatially distributed information. To our knowledge only two other studies, Tenenbaum et al (2006) they showed that lidar-TWIs provided improved predictions of near-surface soil moisture in an urbanizing environment where refined flowpath delineations were necessary, but not in a forested catchment where a coarser, photogrammetric DEM better captured the more generalized soil moisture patterns.…”
Section: Source Data: Usgs Dems Vs Lidar Demsmentioning
confidence: 85%
See 2 more Smart Citations
“…In general, these studies found that higher-quality vertical information results in appreciable improvements in the representation of topographic surfaces, more accurate delineations of hydrologically relevant parameters and more appropriate model outputs, especially regarding spatially distributed information. To our knowledge only two other studies, Tenenbaum et al (2006) they showed that lidar-TWIs provided improved predictions of near-surface soil moisture in an urbanizing environment where refined flowpath delineations were necessary, but not in a forested catchment where a coarser, photogrammetric DEM better captured the more generalized soil moisture patterns.…”
Section: Source Data: Usgs Dems Vs Lidar Demsmentioning
confidence: 85%
“…To some extent, discrepancies in TWIsoil moisture correlations of the previously mentioned studies may be due to variations in the accuracy of the underlying DEM data. Only a few studies have specifically examined the advantages of lidar-derived TWIs relative to other less precise DEM sources, such as the standard USGS 10 m DEMs (e.g., Tenenbaum et al, 2006;Murphy et al, 2009).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution topographic information from lidar has proved important for stream channel delineation (Kinzel et al, 2013), rating curve estimation (Nathanson et al, 2012;Lyon et al, 2015), floodplain mapping and inundation (Marks and Bates, 2000;Kinzel et al, 2007), and topographic water accumulation indices (Sørensen and Seibert, 2007;Jensco et al, 2009). Lidar measurements of micro-topography shows potential for improving soil property and moisture information (e.g., Tenenbaum et al, 2006), surface and floodplain roughness (Mason et al, 2003, Forzieri et al, 2010Brasington et al, 2012;Brubaker et al, 2013), hydraulic dynamics and sediment transport McKean et al, 2014), surface ponding and storage volume calculations (Li et al, 2011;French, 2003), and wetland delineation (e.g., Lane and D'Amico, 2010). Certain hydrological modeling fields are well poised to utilize high-resolution topography, such as movement of water in urban environments (Fewtrell et al, 2008), in-channel flow modeling (Mandlburger et al, 2009;Legleiter et al, 2011), and hyporheic exchange and ecohydraulics in small streams (e.g., Wheaton et al, 2010b).…”
Section: Advances In Hydrology Using Lidarmentioning
confidence: 99%
“…The refinement in topographic accuracy and resolution can also improve physically-based models, such as landslide hazard predictions (Tarolli and Tarboton, 2006) or estimates of soil moisture across the forested landscape (Tenenbaum et al, 2006). (Gaedeke, 2006;Hickman, 1993;Sawyer and Keeler-Wolf, 1995) Latin name and author Common name Mountains due to the prevalence of these features.…”
Section: Applications In Hydrology and Geomorphologymentioning
confidence: 99%